People management: a descriptive analysis of employee experience in junior enterprises - Campos, Amanda Alves; Irikawa, Felipe Segateli; Mansanera, Adriano Rodrigues; Shirabayashi, Juliana Verga; Molin Filho , Rafael Germano Dal (Brazilian Journal of Production Engineering, 2024)
Business relationships are conducted by humans serving other humans. In this context, it becomes essential to analyze Human Resource Management (HRM) in these organizations from the perspective of their employees. Among the models for analyzing HRM, the Employee Experience (EX) model emerges, originating from the Information Age. This study analyzed the HRM of Junior Enterprises (JEs) through the EX-perspective as perceived by their employees. The research was based on the Employee Experience Score (EXS) method. A survey questionnaire was structured based on 17 attributes of the physical, technological, and cultural environments for the research intervention. The results obtained from the participation of members from ten JEs in five Brazilian states indicated that 90% of the JEs were classified with good experiential performance. Furthermore, it was found that the JEs are well-rated when compared to globally renowned organizations.